Pengembangan Komik Edukasi Keselamatan Lalu Lintas untuk Remaja di Cirebon. - Rosyid, Dzulfiqar Fickri; Rachmawati, Ine; Khodijah, Tiara (Universitas Komputer Indonesia, 2025)
Traffic safety is a crucial issue that requires serious attention, particularly among adolescents, who often constitute one of the most vulnerable groups in traffic accident statistics. Their risk-taking behavior and lack of driving experience make them highly susceptible to road-related incidents. The recent surge in traffic violations and accidents involving students in Cirebon City highlights the urgent need for educational interventions that are both communicative and contextually relevant. This study employs a qualitative case study approach with a design-based component, aiming not only to explore adolescent perceptions of traffic safety but also to develop a culturally appropriate print comic as an educational medium. The research was conducted at SMAK Terang Bangsa Cirebon, selected as a representative site for contextualizing comic-based intervention. Data were collected through semi-structured interviews, non-participant observation, and thematic content analysis of student responses. The research was carried out in two phases: an initial exploratory stage to understand students’ knowledge, behaviors, and media preferences, followed by the design and evaluation of a comic showcase tailored to their socio-cultural realities. The findings suggest that comics can effectively convey traffic safety messages in a relatable and engaging manner, stimulate personal reflection, and raise awareness of safer driving behaviors among high school students. These results demonstrate the potential of thematically designed educational comics as an alternative medium for promoting traffic safety awareness among adolescents, especially within the context of urban secondary education. Keywords: Cirebon, Comics, Traffic, Adolescents, Case Study